STRUKTUR PEMBIAYAAN MUDHARABAH DAN MURABAHAH PADA PT. BANK TABUNGAN NEGARA KANCA SYARIAH MAKASSAR - Abdul Khalik (AkMen JURNAL ILMIAH, 2011)
Structural Cost Mudharabah and Murabahah at PT. Bank Tabungan Negara Kanca Syariah Makassar”, The Collage of Economic Nobel Indonesia Makassar. The Title of this thesis was discussed on 25 of January 2010 and received in order conduct research in PT. Bank Tabungan Negara Kanca Syariah Makassar that allocated at Boulevard Ruko Jasfer II No. 34 Makassar city. Though using a timing interval as long as more than two months. Data collection was taken from PT. Bank Tabungan Negara Kanca Syariah Makassar, at financial Departement of cost realitation Mudharabah and Murabahah period 2008, 2009 and 2010 years. After exploring and explaning the result of the study for there years lately, the writer concluded analysis structural cost Mudharabah for 2008 is 16%, 2009 is 65 %, and 2010 is 34%. And analysis structural cost Murabahah for 2008 is 65 %, 2009 is 18 % and 2010 is 34 %.